Software used to simulate IoT solutions Examining my vehicles - Polat, Berna; Das, Resul (Ieee, 2019)
Internet-based digital transformation process of world countries is increasing rapidly. With the spread of the Internet, IoT-based technological solutions continue to increase in this process. Academic and commercial studies on internet based solutions are increasing day by day. Supply of physical equipment, implementation of applications and obtaining results are not very easy and cheap. Therefore, simulation platforms are used for IoT solutions developed for different workspaces and applications. In this paper, some preferred simulation tools for IoT solutions and application areas are examined and a comparative analysis of these tools is given.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 21-22, 2019 -- Inonu Univ, Malatya, TURKEY
Keywords: IoT simulasyon araclari; IoT cozitmleri; Nesnelerin interneti